2018
DOI: 10.3389/fcell.2018.00073
|View full text |Cite
|
Sign up to set email alerts
|

Lamin A, Chromatin and FPLD2: Not Just a Peripheral Ménage-à-Trois

Abstract: At the nuclear periphery, the genome is anchored to A- and B-type nuclear lamins in the form of heterochromatic lamina-associated domains. A-type lamins also associate with chromatin in the nuclear interior, away from the peripheral nuclear lamina. This nucleoplasmic lamin A environment tends to be euchromatic, suggesting distinct roles of lamin A in the regulation of gene expression in peripheral and more central regions of the nucleus. The hot-spot lamin A R482W mutation causing familial partial lipodystroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In FPLD2, it was observed that lamin A connection with chromatin at the nuclear periphery and in the nuclear interior could be affected and associated with tridimensional rearrangements of chromatin [ 128 ]. 3D genome models of fibroblasts from FPLD2 patients have shown a repositioning in the nuclear center of the T/Brachyury gene, a key regulator of mesodermal differentiation, an event favoring gene transcription [ 129 ].…”
Section: Fpld2mentioning
confidence: 99%
“…In FPLD2, it was observed that lamin A connection with chromatin at the nuclear periphery and in the nuclear interior could be affected and associated with tridimensional rearrangements of chromatin [ 128 ]. 3D genome models of fibroblasts from FPLD2 patients have shown a repositioning in the nuclear center of the T/Brachyury gene, a key regulator of mesodermal differentiation, an event favoring gene transcription [ 129 ].…”
Section: Fpld2mentioning
confidence: 99%
“…With the significant changes at the nuclear lamina between the pluripotent state and the somatic/lineage situation it seems unlikely that there are not changes with respect to LADs associating with the nuclear lamina, even though they have not been revealed. Indeed, LADs can also be internally located near A-type lamins (Briand et al, 2018) and so genome organization would be expected to change substantially after the A-type lamins arrive (Figure 3).…”
Section: How Aneuploidies Arisementioning
confidence: 99%